Pengaruh Return on Asset dan Debt to Equity Ratio Terhadap Pengungkapan Islamic Social Reporting Dengan Moderating Kinerja Lingkungan - supendri, Winda; Usdeldi; Orinadi, Mohammad (Universitas Sains dan Teknologi Komputer, 2024)
. This research was conducted with the aim of examining the effect of Return on Assets and Debt to Equity Ratio on disclosure of Islamic Social Reporting by moderating environmental performance. The sample in this study were 11 mining sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2019-2022 period. The type of research method used in this research is quantitative research. The sampling technique used purposive sampling with data analysis used is panel data regression. The analysis used in this study is Moderated Regression Analysis (MRA) and assisted by the EViews 12 analysis tool. Based on the results of this study it can be concluded that Return on Assets has a positive effect on disclosure of Islamic Social Reporting, but the Debt to Equity Ratio has no significant effect on disclosure of Islamic Social reporting. Meanwhile, environmental performance is not able to moderate the relationship between Return on Assets and Debt to Equity Ratio to disclosure of Islamic Social Reporting.